Adenosquamous carcinoma of gall bladder – A rare but aggressive entity - Mahla, Rohit; Gupta, Prakriti; Iyengar, Sudha (Journal of Pathology of Nepal, 2025)
Adenosquamous and squamous cancer of the gall bladder are rare cancers with an incidence of only 5-10 % of total gall bladder malignancies. A 40-year female with complaints of nausea, pain in the abdomen, vomiting for 1 year, and jaundice for 2 years presented to the OPD. CECT revealed a gall bladder fossa mass with choledocolithiasis and dilated CBD, hepatosplenomegaly, and mesenteric lymphadenopathy. Histopathological examination done after surgery diagnosed as adenosquamous cancer of the gall bladder. When compared to adenocarcinoma, squamous cell carcinoma is a highly malignant neoplasm presenting at an advanced stage. Histologically, adenosquamous carcinomas show an admixed malignant glandular and squamous component. The squamous component is reported to grow twice as fast as the adenocarcinoma component. Squamous differentiation of malignancy in the gall bladder is a rare occurrence with poorer prognosis because the tumor tends to be bulky and locally infiltrative at presentation.